Strategies for the Preservation of Historic Areas within Existing Middle Eastern Cities: The Case of Historic Jeddah - Mohammed Aloshan; Islam Elghonaimy; Essam Mesbah; Moustafa Gharieb; Khaled Mahmoud Heba; Mohammed Humaid Alhumaid (Buildings, 2024)
During the recent founding of Saudi Arabia in 1932, there was no interest in the urban and architectural heritage that Jeddah possesses. As a result, historic Jeddah was exposed to many problems similar to many historical Middle Eastern cities. For example, the historic city wall and many heritage buildings were demolished. With the economic recovery during the 1970s, the original dwellers abandoned the city altogether. They were soon replaced by a class of ex-patriate workers who would inhabit the area, and the city’s distinct heritage fell into neglect. At the beginning of the 1980s, attempts to preserve that area began with the expert Robert Matthew, who studied the remaining historical buildings and proposed strategies for preservation that were based on three main directions: restoration, replacement, or new construction. The issuance of “Saudi’s 2030 vision” included programs to develop Saudi cities, including Jeddah. This program includes the removal of unplanned and slum areas around historic Jeddah without developing a clear master plan for what will replace them. In addition, it includes the complete expropriation of historic Jeddah, without announcing a specific plan for what the area will be used for. Therefore, this study seeks to review current preservation strategies, with the aim of reaching results related to the challenges facing the area; demonstrating the effectiveness of the preservation strategies used; and deducing what could contribute in the future to the development, preservation, and optimal exploitation of the area, without losing its value as a result of the modernization processes currently taking place.